PENGARUH KUALITAS PELAPORAN KEUANGAN DAN JATUH TEMPO UTANG TERHADAP EFISIENSI INVESTASI - Alisya Misitama Sakti; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of financial reporting quality and short-term debt maturity on investment efficiency. This study also examine how short-term debt maturity moderates the effect of financial reporting quality on investment efficiency. The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2012. Sampling method used is purposive sampling. A criterion for firm is non financial services firm. Total data of this study is 128 data. Multiple regression with Ordinary Least Square (OLS) method used to be analysis technique. The empirical result of this study show that financial reporting quality and short-term debt maturity have positively sifnificant influenced on investment efficiency. In addition, there no significant effect on the level of use of short term debt on financial reporting quality and investment efficiency.